2007
DOI: 10.3346/jkms.2007.22.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Detection of a Congenital Pancreatic Cyst by Ultrasound

Abstract: We present a case of a fetal pancreatic cyst, a rare disease in fetal life, detected prenatally at 30 weeks' gestation by ultrasound. Routine ultrasound examination at 30 weeks' gestation by primary obstetrician showed a cyst on the fetal abdomen. Initially, the suspected diagnosis was a mesenteric cyst. Subsequent ultrasound examination at weeks 32, 36 showed a fetal retroperitoneal cyst. A 3.6 kg female neonate was born to 23 yr old woman by spontaneous vaginal delivery at 38 weeks' gestation. The fetus unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…Unlike our case with multifocal cysts located in the pancreatic head and tail, Choi et al 13) reported that an isolated 56×47 mm homogenous cyst originating from the pancreatic tail was excised with a distal pancreatectomy. However, excision of the cyst is not always the treatment of choice for all patients.…”
Section: At 36contrasting
confidence: 64%
“…Unlike our case with multifocal cysts located in the pancreatic head and tail, Choi et al 13) reported that an isolated 56×47 mm homogenous cyst originating from the pancreatic tail was excised with a distal pancreatectomy. However, excision of the cyst is not always the treatment of choice for all patients.…”
Section: At 36contrasting
confidence: 64%
“…The neonate expired shortly after delivery due to respiratory failure from pulmonary hypoplasia . Twenty-one reports of prenatally diagnosed lesions have since been published [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] and ours provides the 22nd. These cases primarily describe CPCs as simple-appearing, unilocular cysts of various sizes in the upper abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Complete resection or enucleation should be performed whenever possible, with maximum preservation of the pancreatic tissue [2,4,12,19,22,25,27,32,33,[35][36][37][42][43][44][45]. Distal pancreatectomy is possible when the cyst is located into the pancreatic tail [13,15,17,21,28,31,40,48]. When the cyst is in the pancreatic head, complete removal is not always possible.…”
Section: Discussionmentioning
confidence: 99%